Nonoperative Management of Traumatic Acromioclavicular Joint Injury: A Clinical Commentary with Clinical Practice Considerations - Aaron Sciascia; Aaron J. Bois; W. Ben Kibler (North American Sports Medicine Institute, 2022)
Traumatic injuries of the acromioclavicular joint result in pain and potentially long-term alterations in scapulohumeral rhythm that occurs due to disruption of the clavicular strut function which is integral to scapular kinematics. Nonoperative treatment remains a valid option in most acromioclavicular joint injuries with the potential of minimizing pain and restoring scapulohumeral rhythm. However, few studies have provided nonoperative treatment details. Therefore, the purpose of this clinical commentary is to discuss the rationale, indications, and techniques of nonoperative treatment and present an organized approach for evaluating and managing such patients based on the best available evidence. Attention will be focused on identifying the treatment methods employed and the results/outcomes of such treatments. # Level of Evidence 5